Vestibular Aqueduct Measurements in the 45° Oblique (Pöschl) Plane - Juliano, A.F.; Ting, E.Y.; Mingkwansook, V.; Hamberg, L.M.; Curtin, H.D. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: The 45° oblique (Pöschl) plane allows reliable depiction of the vestibular aqueduct, with virtually its entire length often visible on 1 CT image. We measured its midpoint width in this plane, aiming to determine normal measurement values based on this plane.MATERIALS AND METHODS: We retrospectively evaluated temporal bone CT studies of 96 pediatric patients without sensorineural hearing loss. Midvestibular aqueduct widths were measured in the 45° oblique plane by 2 independent readers by visual assessment (subjective technique). The vestibular aqueducts in 4 human cadaver specimens were also measured in this plane. In addition, there was a specimen that had undergone CT scanning before sectioning, and measurements made on that CT scan and on the histologic section were compared. Measurements from the 96 patients' CT images were then repeated by using findings derived from the radiologic-histologic comparison (objective technique).RESULTS: All vestibular aqueducts were clearly identifiable on 45° oblique-plane CT images. The mean for subjective measurement was 0.526 ± 0.08 mm (range, 0.337–0.947 mm). The 97.5th percentile value was 0.702 mm. The mean for objective measurement was 0.537 ± 0.077 mm (range, 0.331–0.922 mm). The 97.5th percentile value was 0.717 mm.CONCLUSIONS: Measurements of the vestibular aqueduct can be performed reliably and accurately in the 45° oblique plane. The mean midpoint width was 0.5 mm, with a range of 0.3–0.9 mm. These may be considered normal measurement values for the vestibular aqueduct midpoint width when measured in the 45° oblique plane.LVAlarge vestibular aqueductOPAoptimal percentage attenuation